Preparation of PLA Nanoparticles and Study of Their Influencing Factors - Xinyu Zhang; Qing Luo; Fengying Zhang; Xinye Zhao; Ying Li; Ning Yang; Liangshan Feng (Molecules)
Nanoparticles (NPs) have attractive properties that have received impressive consideration in the last few decades. Polylactic acid nanoparticles (PLA-NPs) stand out as a biodegradable polyester with excellent biocompatibility. This investigation introduces PLA-NPs prepared by using the emulsification-solvent volatilization (O/W) method. The effects of ultrasonication time, organic-to-aqueous phase volume ratio, surfactant Tween-20, and PLA on particle size as well as the polydispersity index (PDI) were investigated using a one-factor combination with Response Surface Methodology (RSM). The result indicates that, on the one hand, PLA was the key factor affecting particle size, which gradually increased as the amount of PLA increased from 0.01 to 0.1 g. The particle size of NPs gradually decreased as the surfactant Tween-20 increased from 0.25 mL to 1 mL in the aqueous phase. The volume ratio of the organic phase to the aqueous phase increased from 1:10 to 1:1, with the particle size initially decreasing (from 1:10 to 1:5) and subsequently increasing (from 1:5 to 1:1). As the ultrasonication time increased from 20 min to 40 min, the particle size initially increased (from 25 to 30 min) and then decreased (from 30 to 40 min). On the other hand, Tween-20 was the main factor of PDI, and with the increase of Tween-20, PDI changed significantly and increased rapidly. The volume ratio of the organic phase to the aqueous phase increased from 1:10 to 1:1, resulting in the stabilization and subsequent gradual decrease of the PDI. With the increase of ultrasonication time (20–40 min), PDI tended to be stable after the increase. The effect of PLA on PDI was not significant, and the change of PLA concentration did not cause a significant change in the size of PDI.